(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This systematic literature review explores the relationship between cultural orientations and personality traits. Cultural orientations refer to the values, beliefs, and behaviors that individuals acquire from their cultural contexts, while personality traits are enduring patterns of thoughts, feelings, and behaviors that shape an individual’s overall character. The review aims to synthesize existing research findings on how cultural orientations influence various aspects of personality, including the Big Five traits (openness, conscientiousness, extraversion, agreeableness, and neuroticism), as well as other culturally specific personality dimensions.